Pengaruh Kepemilikan Manajerial, IOS, Laverage dan Profitabilitas terhadap Kualitas Laba - Dea Safira; Hesty Ervianni Zulaecha; Hamdani, Hamdani; Husna Darra Sarra (Jurnal Publikasi Ilmu Manajemen, 2022)
The purpose of this study is to determine the effect of managerial ownership, ios, and leverage on earnings quality in consumer goods industry companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 6 years, namely the 2016-2021 period.The population of this study includes all companies listed on the Indonesia Stock Exchange for the period 2016-2021. The sampling technique used was purposive sampling technique. Based on the predetermined criteria, 12 companies were obtained. The type of data used was secondary data obtained from the Indonesia Stock Exchange website.The analytical method used is panel data regression analysis using the eviews 9.0 data processing program. The results show that managerial ownership has a positive effect on earnings quality, while ios and leverage have no effect on earnings quality.